2006
DOI: 10.1186/1475-2891-5-19
|View full text |Cite
|
Sign up to set email alerts
|

36 year old man presenting with pancreatitis and a history of recent commencement of orlistat case report

Abstract: Background: Orlistat is an anti-obesity drug licensed in the United Kingdom for 7 years. We present a case of a patient who developed pancreatitis four days after commencing orlistat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
0
16
0
1
Order By: Relevance
“…Currently, orlistat is the only FDA (Food and Drug Administration) approved drug for long term management of obesity [14] . It has been reported that there has been an association between the use of orlistat and development of pancreatitis in some cases clinically with no evidence of biliary disease or alcohol consumption [15] . This study is concerned with the description of structural changes in rat pancreas following orlistat administration and whether these effects are dose dependent or not.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, orlistat is the only FDA (Food and Drug Administration) approved drug for long term management of obesity [14] . It has been reported that there has been an association between the use of orlistat and development of pancreatitis in some cases clinically with no evidence of biliary disease or alcohol consumption [15] . This study is concerned with the description of structural changes in rat pancreas following orlistat administration and whether these effects are dose dependent or not.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal failure with oxalate crystal deposition [158,159] Gastro-esophageal reflux disease [160] Additive adverse GI events with olestra-containing foods [161] Increased INR after the addition of orlistat [104] Two women with bulimia nervosa used orlistat to purge following binge [162] Acute kidney injury secondary to acute oxalate nephropathy [163] Myopathy after 27 months of orlistat [164] Acute pancreatitis [165] Jaundice and acute cholestatic hepatitis [166] Hepatocellular necrosis [167] Cutaneous leukocytoclastic vasculitis [168] Diabetic ketoacidosis [169] GI: Gastrointestinal; INR: International normalized ratio. where the lack of effect on sustained linear growth and lack of potential for development of dependency assume even greater importance.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The published version will differ from this one as a result of linguistic and technical corrections and layout editing. 8 …”
Section: Wwwftbcomhrmentioning
confidence: 99%
“…Although orlistat has displayed very promising results for obesity treatment, unfortunately it is associated with a number of unpleasant gastrointestinal side effects (8). Natural products provide an ample scope for the discovery of pancreatic lipase inhibitors that can perhaps be developed into anti-obesity drugs (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%